SEABED TOPOGRAPHY MAPPING IN SANGIHE TALAUD WATERS USING MULTIBEAM ECHOSOUNDER - Haryanto, Dwi; Irfan, Muhamad; Wiguna, Taufan; Febriawan, Hendra Kurnia (Laboratory for Marine Survey Technology, 2020)
The application of multibeam echosounder for seabed topography has been developing rapidly. Multibeam echosounder is a very efficient way to get a wide seabed topography coverage for each ping, so it can produce high-resolution seabed topography maps. These maps can be used as a reference for further investigation or exploration, for example geological studies, marine habitats and others. RV Baruna Jaya IV is operated by Laboratory for Marine Survey Technology – BPPT that have been hull mounted equipped a Germany technology multibeam echosunder Seabeam 1050D system. The Seabeam 1050D allow to sweep measuring the seabed topography using 126 beams simultaneously from port to starboard sites. R.V. Baruna Jaya IV and the Okeanos Explorer of NOAA have been conducted joint Indonesia - U.S. Expedition to Sangihe Talaud waters (INDEX SATAL) in the north area of the North Sulawesi Province during July - August, 2010. Seabed topography of less than 2000 metres were recorded by Seabeam 1050D system, the area of larger depths of 2000 metres to 6000 metres recorded by Simrad EM-302 from Okeanos Explorer. The seabed topography in Sangihe Talaud waters has a varied seabed topography. The new discovery that showed on the map is a 1600 m height of seamount, risen up from the depth of 2300m to 710m. Others geological seabed can be identified according to high resolution bathymetry map resulted from this study.Keywords: multibeam echosounder, seabed topography, seamount, Sangihe Talaud